2012
DOI: 10.5005/jp-journals-10024-1151
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study to Determine the Wettability and Castability of Different Elastomeric Impression Materials

Abstract: Aim:The aim of this study was to determine the wettability of different hydrophilic and hydrophobic elastomeric impression materials and the gypsum castability. Materials and methods:The wettability was evaluated by determining the contact angles of different elastomeric impression materials. The contact angle was determined by placing a drop of aqueous solution of calcium sulfate dihydrate on the flat surface of impression material and specimens were measured using a profile projector.Gypsum castability was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…The result of the present study showed that the mean contact angle of VPES hybrids was (69.6); polyether was (79.2) and the mean contact angle produced by the hydrophilic polyvinylsiloxane (Express) was (87), one minute after mixing. This was in agreement with several studies [ 24 , 40 ], which stated that polyether behaves more hydrophilic during the process of setting and can therefore exhibit better flow properties compared to PVS materials.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The result of the present study showed that the mean contact angle of VPES hybrids was (69.6); polyether was (79.2) and the mean contact angle produced by the hydrophilic polyvinylsiloxane (Express) was (87), one minute after mixing. This was in agreement with several studies [ 24 , 40 ], which stated that polyether behaves more hydrophilic during the process of setting and can therefore exhibit better flow properties compared to PVS materials.…”
Section: Discussionsupporting
confidence: 93%
“…The contact angle values (the angle between the tangent of the symmetrical water droplet and the interface between the droplet and the surface of the impression material) for all specimens were calculated with the use of Auto CAD 2012 (Autodesk Inc, CA, USA) software (Fig. 4 a–c) [ 24 ]. All values gained in this experiment were relative measurements and can therefore only be used in this or similar experimental setups to compare the materials under investigation with each other.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrophobic and hydrophilic properties of the elastomeric material will dictate how well they interact with the gypsum slurry to create a void-free die. 46 This outcome was consistent with research done by Vrbova et al 31 in which scanning electron microscopy, micro computed tomography, and Light microscopy were used to assess the dimensional changes. It was discovered that elastomeric impression materials have very good resistance to the disinfectants.…”
Section: Compatibility With Gypsum Productssupporting
confidence: 88%
“…However, the traditional method has inherent errors due to the shrinkage of the impression material during polymerization and expansion of the gypsum. The dimensional stability of the impression materials is also affected by the temperature, the time taken to make a model after taking the impression, the surface wettability of the gypsum, and the disinfection process [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%